Is Braden Scale Reliable and Sufficient to Evaluate the Risk of Pressure Ulcer Occurrence in Level 3 Intensive Care Unit Patients? - Gul, Yasar Gokhan; Koprulu, Ali Sefik; Haspolat, Ali; Uzman, Sinan; Toptas, Mehmet; Kurtulus, Idris (Aves, 2016)
Objective: To prevent pressure ulcer, detecting risk factors and planning how to act with respect to patients provide to find solution. Thus, Braden Scale is the most common tool that is used in Turkey. This study aimed to measure Braden Scale effectiveness at detecting the risk groups of level 3 intensive care unit patients. Methods: This prospective, single-center study includes 206 level 3 intensive care unit patients whose risk factors were standardized as much as possible in the intensive care unit between January 2014 and May 2015. Routine clinical care was applied to the patients whose risk groups were determined by Braden Scale, and the patients were divided into two groups depending on the presence of a pressure ulcer before discharging from the hospital. Demographic findings, hospitalization duration, mental status, Apache II score, expected/ actual mortality, blood albumin levels, and Braden Scale score were compared. Results: Comparison of the groups showed that patients' age, length of stay in intensive care unit, mental status, and blood albumin levels are significantly different between patients with and without pressure ulcers. Furthermore, scores of patients with pressure ulcers were not significantly different from those of patients without pressure ulcers. Data also illustrated that pressure ulcers occurred in no risk patients with the ratio of 7.14%; in low-risk patients with the ratio of 27.8%; in moderate-risk patients with the ratio of 29.73%; in high-risk patients with the ratio of 17.72%. Conclusion: Data evaluation demonstrates that Braden Scale is not effective to detect the risk factors, and parameters related to pressure ulcer development are not sufficiently represented by Braden Scale. Modification of an existing scale or a new risk assessment scale that includes all other risk parameters and that is more suitable for the patients of our country is required.
Keywords: Braden Risk Assessment Scale; Pressure Ulcer; İntensive Care Unit; Predictive-Validity; Surgical-Patients; Prevalence; Index; Sores